Sertoli-Leydig Cell -A Rare Male Hormone Producing Ovarian Tumor - Khalida Nasreen; Rozina Mustafa (Journal of Bahria University Medical and Dental College)
Sertoli-Leydig cell tumor (SLCT) of ovary is an unusual neoplasm that belongs to a group of sex cord-stromal tumors of ovary. It accounts for less than 0.5% of all primary ovarian neoplasms. We report a case of primary intermediate ovarian Sertoli-Leydig cell tumor (SLCT) involving the left ovary in a 32-year-old nulliparous woman who presented with history of secondary amenorrhea for 8 months, hirsutism, and voice changes